The Characterization of Foam Glass Ceramic Based on Industrial Solid Waste - Isnugroho, Kusno; Hendronursito, Yusup; Asmi, Dwi (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2023)
An initial characterization of the raw materials for manufacturing foam glass ceramics has been done using raw materials derived from industrial solid waste. The raw material is in the form of fly ash, a waste of coal combustion in steam power plants, stone crusher industrial waste in the form of basalt rock ash, glass bottle waste, and used aluminum smelting waste. The initial characterization was done by analyzing the chemical composition using the XRF method, identifying the crystalline phase in the raw materials using the XRD method, and morphological analysis using SEM. From the results of raw material analysis, the dominant chemical composition is SiO2, CaO, Fe2O3, and Al2O3 compounds. At the same time, the glass-ceramic foam formed has wollastonite, anorthite, and diopside crystalline phases. The pore structure formed is a closed pore.